The ethics of preconception expanded carrier screening in patients seeking assisted reproduction. Issue 1 (12th February 2021) - de Wert, Guido; van der Hout, Sanne; Goddijn, Mariëtte; Vassena, Rita; Frith, Lucy; Vermeulen, Nathalie; Eichenlaub-Ritter, Ursula; ,
ABSTRACT: Expanded carrier screening (ECS) entails a screening offer for carrier status for multiple recessive disorders simultaneously and allows testing of couples or individuals regardless of ancestry or geographic origin. Although universal ECS—referring to a screening offer for the general population—has generated considerable ethical debate, little attention has been given to the ethics of preconception ECS for patients applying for assisted reproduction using their own gametes. There are several reasons why it is time for a systematic reflection on this practice. Firstly, various European fertility clinics already offer preconception ECS on a routine basis, and others are considering such a screening offer. Professionals involved in assisted reproduction have indicated a need for ethical guidance for ECS. Secondly, it is expected that patients seeking assisted reproduction will be particularly interested in preconception ECS, as they are already undertaking the physical, emotional and economic burdens of such reproduction. Thirdly, an offer of preconception ECS to patients seeking assisted reproduction raises particular ethical questions that do not arise in the context of universal ECS: the professional's involvement in the conception implies that both parental and professional responsibilities should be taken into account. This paper reflects on and provides ethical guidance for a responsible implementation of preconception ECS to patients seeking assisted reproduction using their own gametes by assessing the proportionality of such a screening offer: do the possible benefits clearly outweigh the possible harms and disadvantages? If so, for what kinds of disorders and under what conditions?